2015 IEEE International Symposium on Antennas and Propagation &Amp; USNC/URSI National Radio Science Meeting 2015
DOI: 10.1109/aps.2015.7304563
|View full text |Cite
|
Sign up to set email alerts
|

Switched sensor array for near-field microwave imaging of tissue

Abstract: This paper describes the design of an electronicallyswitched active antenna array for near-field microwave imaging of tissue in the range of 6 to 8 GHz. Each antenna element connects directly to a dedicated radio front-end, whose intermediate frequency output is fed to a common port for digital data processing. In this way, the difficulties of designing reproducible microwave switching and feeding networks are avoided. Within each front-end, switched-bias low-noise amplifiers are used to maximize the differenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…A bias-switched UWB radio sensor for tissue imaging was first proposed in [ 31 , 32 ], where mixed-signal simulations suggested that a dynamic range as high as 127 dB can be achieved provided the IF receiver noise floor is sufficiently low, i.e., dBm at a resolution bandwidth of 1 Hz. Here, we show the experimental results with a prototype of the radio sensor, which demonstrate a dynamic range of 118 dB when the resolution bandwidth is set at 100 Hz.…”
Section: Introductionmentioning
confidence: 99%
“…A bias-switched UWB radio sensor for tissue imaging was first proposed in [ 31 , 32 ], where mixed-signal simulations suggested that a dynamic range as high as 127 dB can be achieved provided the IF receiver noise floor is sufficiently low, i.e., dBm at a resolution bandwidth of 1 Hz. Here, we show the experimental results with a prototype of the radio sensor, which demonstrate a dynamic range of 118 dB when the resolution bandwidth is set at 100 Hz.…”
Section: Introductionmentioning
confidence: 99%
“…We briefly note that the mutual coupling of neighboring array elements (measured to be below −15 dB [21]) is of no concern in a bias-switched array [16]. The isolation of the receiving elements is near-perfect [24], [25] because, at each measurement, only the UWB receiver attached to the "activated" element is ON while those of all other elements are OFF. Finally, we note that reoptimizing the array for different tissue electrical properties must focus on substrate permittivity, slot size, array-element spacing, and position of the coaxial connector relative to the fork.…”
Section: Discussionmentioning
confidence: 98%